2012
DOI: 10.5194/isprsarchives-xxxviii-5-w12-97-2011
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality Based Scale Selection in 3d Lidar Point Clouds

Abstract: ABSTRACT:This papers presents a multi-scale method that computes robust geometric features on lidar point clouds in order to retrieve the optimal neighborhood size for each point. Three dimensionality features are calculated on spherical neighborhoods at various radius sizes. Based on combinations of the eigenvalues of the local structure tensor, they describe the shape of the neighborhood, indicating whether the local geometry is more linear (1D), planar (2D) or volumetric (3D). Two radius-selection criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
213
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(235 citation statements)
references
References 16 publications
(11 reference statements)
1
213
0
Order By: Relevance
“…Furthermore, identical values for the scale parameter are typically selected for all points of the 3D point cloud. Recent investigations however revealed that structures related with different classes may favor a different neighborhood size (Weinmann et al, 2015a;Weinmann, 2016) and therefore it seems favorable to allow for more variability by using data-driven approaches for optimal neighborhood size selection (Mitra and Nguyen, 2003;Lalonde et al, 2005;Demantké et al, 2011;Weinmann et al, 2015a).…”
Section: Neighborhood Recoverymentioning
confidence: 99%
“…Furthermore, identical values for the scale parameter are typically selected for all points of the 3D point cloud. Recent investigations however revealed that structures related with different classes may favor a different neighborhood size (Weinmann et al, 2015a;Weinmann, 2016) and therefore it seems favorable to allow for more variability by using data-driven approaches for optimal neighborhood size selection (Mitra and Nguyen, 2003;Lalonde et al, 2005;Demantké et al, 2011;Weinmann et al, 2015a).…”
Section: Neighborhood Recoverymentioning
confidence: 99%
“…The methods in this category analyze the point cloud characteristics (Demantke et al, 2011, Weinmann et al, 2015. They consider different properties of the PCA of the neighborhood of each point in order to perform a semantic segmentation.…”
Section: Statistical Segmentationmentioning
confidence: 99%
“…From each planar segment, four features were extracted: the number of points per segment, average residual to the plane, inclination angle and maximal height difference to the surrounding points. The local neighborhood features are based on the observation that the ratio between the eigenvalues of the covariance matrix of the XYZ coordinates of a point's nearest neighbors can represent the shape of the local neighborhood [37]. For example, the relative proportions between these eigenvalues may describe the local neighborhood as being planar, linear or scattered.…”
Section: Feature Extraction From Uav Datamentioning
confidence: 99%